2023
DOI: 10.3390/ijms241512419
|View full text |Cite
|
Sign up to set email alerts
|

CSB Regulates Pathway Choice in Response to DNA Replication Stress Induced by Camptothecin

Abstract: Topoisomerase inhibitor camptothecin (CPT) induces fork stalling and is highly toxic to proliferating cells. However, how cells respond to CPT-induced fork stalling has not been fully characterized. Here, we report that Cockayne syndrome group B (CSB) protein inhibits PRIMPOL-dependent fork repriming in response to a low dose of CPT. At a high concentration of CPT, CSB is required to promote the restart of DNA replication through MUS81–RAD52–POLD3-dependent break-induced replication (BIR). In the absence of CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…To investigate whether PRIMPOL mediates unrestrained fork progression in CSB-KO cells, we knocked down PRIMPOL in both U2OS WT and CSB-KO cells (Figure 6C ). DNA fiber analysis revealed that depletion of PRIMPOL abrogated the restoration of the ratio of CldU/IdU in CSB-KO cells in the presence of 50 μM HU (Figure 6D and E ), in agreement with our previous finding that PRIMPOL mediates unrestrained fork progression in CSB-KO cells in response to a low dose of camptothecin (CPT) ( 36 ). PRIMPOL-mediated fork repriming is associated with accumulation of ssDNA gaps ( 64–66 ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…To investigate whether PRIMPOL mediates unrestrained fork progression in CSB-KO cells, we knocked down PRIMPOL in both U2OS WT and CSB-KO cells (Figure 6C ). DNA fiber analysis revealed that depletion of PRIMPOL abrogated the restoration of the ratio of CldU/IdU in CSB-KO cells in the presence of 50 μM HU (Figure 6D and E ), in agreement with our previous finding that PRIMPOL mediates unrestrained fork progression in CSB-KO cells in response to a low dose of camptothecin (CPT) ( 36 ). PRIMPOL-mediated fork repriming is associated with accumulation of ssDNA gaps ( 64–66 ).…”
Section: Resultssupporting
confidence: 91%
“…S1 nuclease assays were done as described ( 36 ). To detect ssDNA gaps, cells were first incubated with 25 μM IdU for 20 min and then 250 μM CldU for 60 min in the presence of 50 μM HU.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation